Funktionsabspaltung des Suffixes "-ig" beim Verbbildungsmuster mit "-igen" - Susumu Kuroda (Zeitschrift für Wortbildung)
This article deals with the development of -igen verbs in German since the Old High German period, demonstrating that this can be regarded as a process in which the adjective formation morpheme -ig gradually develops into a component of a word formation pattern that derives transitive verbs from nouns. An -igen-verb can be descended not only from an -ig-adjective (würdig – würdigen) but also from a noun without an intermediary -ig-adjective (Pein – *peinig – peinigen). In this article, it is claimed that a word formation pattern with -ig develops over time. The emergence of this word formation pattern can be described as a "reanalysis" of the verb structure accompanied by a "resegmentation" of the original word structure and a semantic "remotivation" of the established unit. It is also pointed out that this development is particularly evident in the Middle High German period.